Mesodorylaimus ushkaniensis sp. n. and Allodorylaimus baikalensis sp. n. (Nematoda, Dorylaimida) from Lake Baikal, Russia - Naumova, Tatyana V.; Gagarin, Vladimir G. (Zootaxa, 2021)
Two new nematode species of the order Dorylaimida from Lake Baikal sediments are described and illustrated. Mesodorylaimus ushkaniensis sp. n. is morphologically similar to M. cryptosperma Loof, 1969, but differs by the longer body, comparatively shorter tail in females, longer odontostyle and longer spicules. Allodorylaimus baikalensis sp. n. resembles A. tarkoenensis (Andrássy, 1959) Andrássy, 1986, but differs by the comparatively longer body, tail, spicules, and prerectum in females.